Explaining deviations from Okun's law - Claudia Foroni; Francesco Furlanetto (European Central Bank (ECB), 2022)
Despite its stability over time, as for any statistical relationship, Okun's law is subject to deviations that can be large at times. In this paper, we provide a mapping between residuals in Okun's regressions and structural shocks identified with a SVAR model by inspecting how unemployment responds to the state of the economy. We show that deviations from Okun's law are a natural and expected outcome once one takes a multi-shock perspective, as long as shocks to automation, labour supply and structural factors in the labour market are taken into account. Our simple recipe for policy makers is that, if a positive deviation from Okun's law arises, it is likely to be generated by either positive labour supply or automation shocks or by negative structural factors shocks.
Keywords: E24; E32; C32; 330; Okun’ s law; labour markets; Business cycle fluctuations; Bayesian VAR